Pengembangan Multimedia Pembelajaran Interaktif (MPI) Berbasis Canva Pada Mata Pelajaran Rias Wajah Foto Siswa Kecantikan SMKN 1 Pogalan Trenggalek - Elnanda Putri Jayanti; Biyan Yesi Wilujeng; Nieke Andina Wijaya; Sri Dwiyanti (Program Studi Pendidikan Tata Rias, 2025)
Canva-based interactive learning multimedia (MPI) as a learning medium can create learning that is not repetitive, and students will not feel bored during the learning process. The type of research used is research and development (R&D). The data collection methods used were observation, questionnaires, and tests of cognitive and psychomotor learning outcomes. The results showed that (1) The overall average score of media suitability level reviewed from media, material and language was 4.64 points, and the standard was